How Behavioral Branding Affects Brand Equity - Lieven, Theo (Frontiers in Psychology, 2022)
Maintaining and increasing brand equity is the top priority for most brand managers. This includes not only the areas of public relations and advertising, but also the way in which sales staff communicates regarding the brand. According to behavioral branding, the brand should be strengthened by the brand fit of the employees. To date, research and practice have developed more intuitive and heuristic methods for evaluating employee behavior and its impact on the brand. In this paper, behavior will be operationalized and measured by personality and sales encounter experience. Findings show how behavioral branding has a strong influence on brand equity.